A Comparative Analysis of Equivalent Static and Time History Dynamic Methods: Low-Rise Mall Building Case Study - Kaira Jesusa Prasodjo; Yosafat Aji Pranata (Jurnal Konstruksi dan Infrastruktur : Teknik Sipil dan Perencanaan, 2026)
Earthquake-resistant buildings are structures designed to safely withstand both of lateral and gravity loads. The purpose of this study is to analyze the behavior of the structural, which are stiffness and strength under lateral seismic loads using equivalent static analysis and time history dynamic analysis. The maximum displacement occurs at the 5th floor, reaching 27,34 mm (X-direction) and 29,99 mm (Y-direction). These results, from comparing both analysis methods, remain below the allowable limit of 70 mm per SNI 1726:2019. Strength evaluation, based on internal force demands indicates that beam and column capacities satisfy SNI 2847:2019 requirements. The flexural and shear capacities of beams and columns were verified using the design criteria Mu < ϕMn and Vu < ϕVn, confirming that the structural elements are able to resist the applied bending moments and shear forces safely. In general, the 5-storey mall building in Magelang City shows strength and stiffness behavior that meets the strength and stiffness requirements, using both equivalent static analysis and time history dynamic analysis.